Sustainable Mining: Case Study for Bauxite Mining in Pahang - M. M., Yusoff; Abdul Syukor, Abd Razak; Doh, Shu Ing; Gaanty Pragas, Maniam; Mohamad Idris, Ali; Muzamir, Hasan; Noram Irwan, Ramli; Zulkefli, Yaacob (Academy of Sciences Malaysia, 2017)
Bauxite mining in Kuantan, Pahang started in early 2013 with small-scale mining in Balok and later expanded to Bukit Goh, Bukit Sagu and Sungai Karang. The rapid expansion, from 343,000 tonnes to 3.72 million tonnes from January to September 2015, coupled with uncontrolled and unsustainable legal and illegal mining activities has resulted in an environmental disaster. Government through the Ministry of Natural Resources and Environment first imposed a three-month moratorium on all bauxite mining activities in Pahang on 15 January 2016. However, the moratorium has been extended several times with the current period ending on 31 December 2017 (as of June 2017).